From Folk Ritual to a National Heritage Festival: The Reorganization Process of the Tianhou Pagoda Festival in Binh Duong Province, Vietnam - Dang Thị Kieu Oanh (SUVANNABHUMI, 2025)
Originating from Putian, Fujian (China), the worship of Mazu (Vietnamese: Thiên Hậu) was brought to Southern Vietnam by Chinese migrants and has become deeply embedded in the cultural-religious life of Binh Duong. Once a community-led folk ritual, the annual Tianhou Pagoda Festival in Thu Dau Mot has been gradually institutionalized through state involvement, transforming into a symbol of multicultural identity and a promoted cultural tourism site. Applying the concept of "invented tradition" (Hobsbawm) and Marxist anthropological approaches to political economy, this article examines the restructuring of the festival in Binh Duong. The findings indicate that (1) tradition is not static but continually adapts to economic, social, and historical contexts; (2) restructuring involves cultural negotiations among diverse actors, reflecting the complex interplay within local communities and between these communities and the state; and (3) this process leads to the deconstruction of traditional norms, resulting in new cultural form.